An external control unit implemented for stimulator ASIC testing - E. Noorsal; K. Sooksood; H. Xu; Z. I. Rizman (My University, 2018)
This paper presents the design and development of an external control unit (ECU) for a stimulator ASIC testing purposes. The ECU consists of a graphical user interface (GUI) from the PC, a data transceiver and a power transmitter. The GUI was developed using MATLAB for stimulation data setup. The data transceiver was designed using hardware description language (HDL) Verilog code and was implemented in a Virtex-II Pro FPGA board. The overall stimulator ASIC design architecture and its operation for an epiretinal implant application are briefly explained to correlate with the ECU’s design requirements. The flexible multichannel stimulator ASIC was successfully fabricated in a 0.35μm AMS HVCMOS technology. Conducted simulation and measurement results on stimulation waveform generation, supply voltage compliance and external control of supply voltage adaptation validate the functionality of the designed ECU and the stimulator ASIC.Keywords: external control unit; data transceiver; stimulator ASIC; retinal prosthesis; epiretinal implant; stimulation waveform; Manchester data; voltage compliance.
Keywords: Application-specific integrated circuit; Transceiver; Control unit; Neuroscience and Neural Engineering